1997
DOI: 10.1002/(sici)1098-2302(199701)30:1<61::aid-dev6>3.3.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

The role of the anterior cingulate in automatic and controlled processes: A developmental neuroanatomical study

Abstract: This study examines the role of the anterior cingulate in the development of attention. Task performance relying predominantly on either automatic or controlled processes was correlated with magnetic resonance imaging based measures of the anterior cingulate in 26 normal children ages 5 to 16 years. Attentional measures were assessed with a visual discrimination paradigm. Parasagittal slices from a 3-D, T1-weighted volume data set were used to obtain area measurements of the anterior cingulate. Response latenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
68
0
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(80 citation statements)
references
References 0 publications
10
68
0
2
Order By: Relevance
“…Observation of sex differences may also be confounded given that the males may have been somewhat overrepresented in the upper end of our age range (and volumes decrease with age such that older participants have smaller gray-matter volumes), which could account for the larger subcortical gray-matter volumes in females. Nonetheless, our results are consistent with at least one other report, attesting to their validity (Giedd et al 1997). …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Observation of sex differences may also be confounded given that the males may have been somewhat overrepresented in the upper end of our age range (and volumes decrease with age such that older participants have smaller gray-matter volumes), which could account for the larger subcortical gray-matter volumes in females. Nonetheless, our results are consistent with at least one other report, attesting to their validity (Giedd et al 1997). …”
Section: Discussionsupporting
confidence: 93%
“…This has been shown in one recent study where improvement on a task of verbal learning and organization was found to be related to maturation specifically in the frontal lobes (Sowell et al 2001). Similar relations between cingulate cortex and tasks of attention have been observed (Casey et al 1997) providing further evidence that the structural changes observed are related to improved cognitive abilities.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The sensory selection task was a forced-choice discrimination task (Casey et al, 1993 that required the subject to select which of three objects presented in the center of a computer screen was unique based on stimulus attributes of color and shape. In the control condition, the unique attribute was constant across trials.…”
Section: Behavioral Paradigmsmentioning
confidence: 99%
“…Recent studies have focused on the examination of these late brain maturational changes in vivo using MRI to assess for age-related changes in total brain volume and in the volumes of various cortical and subcortical structures (Jernigan et al 1991;Pfefferbaum et al 1994;Caviness et al 1996;Giedd et al 1996aGiedd et al , 1996bGiedd et al , 1999Reiss et al 1996;Giedd et al 1997;Sowell and Jernigan 1998). In these studies, significant total brain volume increases have been observed between childhood and young adulthood (Jernigan et al 1991, Giedd et al 1999.…”
mentioning
confidence: 99%